Environmentally Benign Water-Soluble Sodium L-2-(1-Imidazolyl) Alkanoic Acids as New Corrosion Inhibitors for Mild Steel in Artificial Seawater - Haque, Jiyaul; Zulkifli, Mohammad F. Ridwan; Ismail, Nabilah; Quraishi, Mumtaz A.; Mohd Ghazali, Mohd Sabri; Berdimurodov, Elyor; Wan Nik, Wan Mohd Norsani Bin (American Chemical Society, 2023)
hree novel natural amino acid-derived sodium L-2-(1-imidazolyl) alkanoic acids (IZSs), namely, sodium 2-(1H-imidazol-1-yl)-4-methylpentanoate (IZS-L), sodium 2-(1H-imidazol-1-yl)-3-phenylpropanoate (IZS-P), and sodium 2-(1H-imidazol-1-yl)-4-(methylthio)butanoate (IZS-M), were investigated as corrosion inhibitors. The IZSs were synthesized following the green chemistry principles, and their structure was characterized using FTIR and NMR techniques. The corrosion study results reveal that a moderate concentration of IZSs (having low solution conductivity) showed potential corrosion inhibition for mild steel in artificial seawater. At longer immersion, IZS-P forms a uniform protective film and exhibits the potential inhibition efficiency of 82.46% at 8.4 mmol L-1. Tafel polarization results reveal that IZS-P and IZS-M act as mixed types with an anodic predominantly corrosion inhibitor. The electrochemical impedance spectroscopy results signify that IZSs inhibit mild steel corrosion through the formation of an inhibitor film on the metal surface, which was further confirmed by the FTIR, SEM, EDX, and XPS studies. DFT result shows that in IZS-P, the benzylic group (−CH2-Ph) has greater electron distribution compared to isobutyl (−CH2CH(CH3)2) in IZS-L and methythioethyl group (−CH2CH2SCH3) which supported the corrosion inhibition performance at longer immersion [IZS-P (82.46%) > IZS-M (67.19%) > IZS-L (24.77%)].
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: alkanoic acids; methylpentanoate (IZS-L); Tafel polarization